2022
DOI: 10.1097/jnn.0000000000000630
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Adaptation to Disease and Self-care Agency Levels in Patients With Multiple Sclerosis

Abstract: BACKGROUND: Multiple sclerosis (MS) is an inflammatory and demyelinating disorder of the central nervous system. The patients with MS have some difficulties in physical, social, and psychological functions. This study was carried out to determine the relationship between the adaptation levels of patients with MS to the disease and their self-care agency levels. METHODS: This study used a descriptive design and was carried out in a university hospital's neurology clinic and outpatient clinic between July 2019 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…4 Another study reported that pwMS adapt to MS physically and psychologically but not socially. 24 These results highlight the importance of understanding emotional and cognitive processes related to adaptation in accepting the presence of MS. 19 In contrast, some participants accepted the follower aspect of MS and gave it a positive meaning (partner MS). Considering that the adaptation levels of individuals who accept MS are stronger and more consistent, 25 acceptance of the existence of MS is pleasing in that it can help the individual relax psychologically and manage MS more effectively.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…4 Another study reported that pwMS adapt to MS physically and psychologically but not socially. 24 These results highlight the importance of understanding emotional and cognitive processes related to adaptation in accepting the presence of MS. 19 In contrast, some participants accepted the follower aspect of MS and gave it a positive meaning (partner MS). Considering that the adaptation levels of individuals who accept MS are stronger and more consistent, 25 acceptance of the existence of MS is pleasing in that it can help the individual relax psychologically and manage MS more effectively.…”
Section: Discussionmentioning
confidence: 91%
“…This perception can have a negative impact on pwMS’ meaningful activities (work, social activities) and interactions 19 . However, despite the negative impact, it is possible that the disease can positively affect the mental health of pwMS 24 . For example, the patient's perception of control over their lives or the ability to reappraise their situation positively may lead to better adaptation 19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations